Family Relationships and Youth Sport: Influence of Siblings and Parents on Youth's Participation, Interests, and Skills - Osai, Keith V; Whiteman, Shawn D (Journal of Amateur Sport, 2017)
Taking a family systems perspective, the present study investigated how older siblings’ and parents’ (mothers’ and fathers’) interests, skills, and participation in sports predicted younger siblings’ attitudes and behaviors in those same domains. Testing social learning principles, we further examined whether family members’ influence was stronger when they shared warmer relationships and siblings shared the same gender. Participants included mothers, fathers, and adolescent-aged first and second-born siblings from 197 maritally intact families. Families participated in home interviews as well as a series of 7 nightly phone calls during which participants reported on their daily activities. Across dependent variables, results revealed that parents’ and (with one exception) older siblings’ qualities were predictive of younger siblings’ interests, skills, and participation in sports. Inconsistent with hypotheses, however, family members’ influence was not moderated by relational warmth. Discussion highlights the need to examine the socialization processes by which siblings shape each other’s sport-related attitudes and activities.